An Assessment of The Effect of The Average Speed Enforcement Systems on Lithuanian Roads - Laura Gavėnienė; Donatas Čygas; Laura Jateikienė Jateikienė; Viktoras Vorobjovas; Vilma Jasiūnienė; Atis Zarinš (The Baltic Journal of Road and Bridge Engineering)
The speeding is a major road safety problem on the roads of Lithuania and many other countries. To reduce and control the speed of vehicles, engineering measures are installed on the roads of Lithuania and other countries – intelligent instantaneous and average speed enforcement systems, as well as many other engineering and structural speed reduction measures. The article presents good practices in the use of average speed enforcement systems, assessment of their effect on road safety. The article analyses the assessment results of the effect of the average speed enforcement systems installed on 25 sections of roads in Lithuania that have been operating for four years. Calculations of the effect factor of the installed average speed enforcement systems on road safety were performed using the before-and-after (B&A) method with a comparison group. Studies on the effect of application of speed control systems provide conditions for evaluating road safety, i.e., changes in road accidents linked to the effectiveness of implemented measures. The conclusions of the conducted study presented the calculations of the efficiency coefficients of the average speed enforcement systems on Lithuanian main and national roads. The analysis of the results of the conducted study allows stating that the installed average speed enforcement systems on 25 sections of Lithuanian roads increase overall road safety by 47%, reduce the number of collisions with animals by 80%, and the number of collisions with vehicles by 35%, as well as the number of other road accidents by 56%.